Science Journalism, Value Judgments, and the Open Science Movement - Elliott, Kevin C. (Frontiers in Communication, 2019)
Science journalists face significant challenges as they seek to report on scientific research in socially beneficial ways. This study draws on recent scholarship in the philosophy of science that can help journalists navigate these challenges. It proposes that science journalists have the opportunity to contribute to the open science movement by identifying and explaining major value judgments in scientific research for members of the public. Journalists are uniquely situated to fulfill this role because they serve as gatekeepers of information for the public and because their investigative skills are ideal for uncovering value judgments. The study concludes by examining a case study of recent journalistic reporting on possible health effects associated with cell phone radiation in order to illustrate how science journalists can adopt this role.